Environmental Science : Society, Nature, and Technology - Akitsu, Takashiro; Pan Stanford Publishing (Singapore : Pan Stanford Publishing, an imprint of Pan Stanford, 2018)
This book presents the current aspects of environmental issues in view of chemical processes particularly with respect to two facets: social sciences along with chemistry and natural sciences. The former facet explores the environmental economics and policies along with chemical engineering or green chemistry and the latter the various fields of environmental studies. The book was conceptualized in the form of e-learning content, such as PowerPoint presentation, with explanatory notes to a new style of lectures on environmental science in a university at undergraduate level. Each chapter of the book comprises a summary of the contents of the chapter; a list of specific terms and their explanation; topics that can be taken up for discussion among college students, mainly freshmen in liberal arts, and for enhancing general knowledge; and problems and solutions using active learning methods.
Part 1: Technology and Society -- 1. Pollution and Environmental Problems -- 2. The Current Situation of the Natural Environment -- 3. Resources and Energy -- 4. Environmental Problems and Chemistry or Chemical Engineering -- 5. Life Cycle Assessment -- 6. Risk Assessment of Chemical Substances -- 7. Chemistry and Environment -- 8. Energy Resource by Chemistry and Technology -- 9. Green Chemistry -- 10. Processing and Recycling by Chemical Engineering -- 11. Sustainable Society -- Part 2: Nature and Substances -- 12. Composition of Global Environment -- 13. Foundations of Energy Science -- 14. Fossil Fuel -- 15. Nuclear Power Generation -- 16. Nuclear Energy and Environment -- 17. Renewable Energy -- 18. Basics of Earth Science -- 19. Air Pollution -- 20. Acid Rain -- 21. Global Warming and Greenhouse Gases -- 22. Fundamentals of Ecology -- 23. Water -- 24. Biosphere and Biodiversity5. Chemical Substances and Wastes.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Environmental / General; TECHNOLOGY & ENGINEERING / Material Science; Environmental sciences; Electronic books